The Role of Pharmacy Management in Improving Patient Safety through the Prevention of Medication Errors: A Literature Review - Novega Diyan Al Amanah Amanah; Nevi Nur Fitriasari Fitriasari; Mey Apriansyah; Wahyu Purwanto; Ika Purwidyaningrum (GLOBAL HEALTH SCIENCE GROUP, 2026)
Medication errors remain a major challenge in patient safety within healthcare facilities and may occur at any stage of the medication use process, including prescribing, preparation, dispensing, administration, and therapeutic monitoring. Such errors have the potential to cause adverse clinical outcomes, increase healthcare costs, and compromise the quality of care. Pharmacy management plays a strategic role in preventing medication errors through the development and implementation of integrated, patient safety–oriented medication management systems. This literature review aims to examine and synthesize findings from scientific journals concerning the role of pharmacy management in improving patient safety through the prevention of medication errors. The literature search was conducted using a narrative review approach of open-access scientific journal articles published within the period of 2019–2024 and retrieved from PubMed Central, Frontiers, BMC Journals, PLOS ONE, and DOAJ. The search was performed using combinations of keywords with Boolean operators as follows: (“pharmacy management” OR “pharmaceutical services” OR “medication management system”) AND (“medication errors”) AND (“patient safety”). A total of 285 records were identified through database searching. After the removal of duplicates and other ineligible records, 180 articles were screened, of which 80 were excluded. Subsequently, 100 full-text articles were assessed, and 30 studies were finally included in this review. articles comprised primary research studies relevant to pharmacy management, medication errors, and patient safety. The findings indicate that the role of pharmacy management in preventing medication errors can be categorized into several key themes, including the management of dispensing and drug distribution systems, optimization of clinical pharmacists’ roles in patient care, implementation of standard operating procedures in medication management, and the utilization of pharmacy technologies and information systems. An integrated pharmacy management approach has been reported to contribute to reducing the incidence of medication errors and enhancing patient safety across various healthcare settings. This review concludes that strengthening pharmacy management constitutes a critical component in efforts to improve patient safety and to develop safer healthcare delivery systems.